Role of Epigenetics in the Pathogenesis and Management of Type 2 Diabetes Mellitus - Yahaya, Tajudeen (Translation: The University of Toledo Journal of Medical Sciences, 2019)
The need to reverse the growing incidence and burden of diabetes mellitus (DM) worldwide has led to more studies on the possible causes of the disease. Genetic and environmental factors had long been suspected in the pathogenesis of a form of the disease known as the Type 2 diabetes mellitus (T2DM). However, more recent studies suggest epigenetic changes could also be involved in the onset of the disease. This review highlights the role of epigenetic modifications in the pathogenesis and management of T2DM. Peer reviewed studies on the subject were retrieved from reputable sources over the internet, and the majority of the studies unanimously implicated epigenetic modifications in the pathogenesis of some cases of the disease. DNA methylation, histone modification and microRNAs mediated pathways were observed to be the main mechanisms of epigenetic changes. These mechanisms are triggered by certain environmental factors such as diets, microbial and pollutant exposure, lifestyles, among others, prior to the onset of T2DM. Epigenetic changes can modify the expressions and functions of certain genes involved in insulin biosynthesis and glucose metabolism, leading to hyperglycemia and insulin resistance, which are hallmarks of T2DM. Fortunately, epigenetic changes can be reversed by blocking or activating the modulating enzymes, thus if the epigenetic aetiology of a diabetic condition is identified, it can be used as a therapeutic strategy.